A systematic review protocol on the epidemiology of zinc deficiency and associated factors during pregnancy in Africa - Melese L Endalifer; Getnet G Azeze; Gedefaw Diress; Asmamaw D Bizuneh; Hanna Demelash (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background Zinc is a trace element which acts as a coenzyme for 200 enzymes. Zinc deficiency has highly correlated with infant morbidity and mortality. Even though zinc deficiency is an emergent public health problem, determinants and magnitude is not well studied in Africa. This study will estimate the pooled prevalence of zinc deficiency in Africa and to identify associated factors for zinc deficiency among pregnant women. # Methods and analysis We will use the following databases: PubMed, Google Scholar, and Cochrane library. Funnel plot and Egger's regression test will be conducted to check potential publication bias. Heterogeneity among the studies will be tested using Higgins method where I2 statistics will be calculated and compared with the standard. Meta regression and sub group analysis will be conducted to identify potential source of heterogeneity. We will include observational studies including case-control, cohort, and cross-sectional studies. The current review will delimit to studies conducted in Africa and published in English language. # Ethics and dissemination Ethics approval and consent are not required. After completing the review, the paper will be submitted to a reputable peer reviewed journal. **PROSPERO registration number**: CRD42019119449.